Electrical modelling and power quality analysis of three-phase X-ray apparatus - Moreira, Alexandre C.; Da Silva, Luiz C. P.; Paredes, Helmo K. Morales [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2014)
This article proposes the use of PSCAD/EMTDC to model and simulate a three-phase x-ray machine. The model is an alternative tool to power quality studies, load connection impact analysis and power factor correction in the electric power distribution systems. The developed model is used to identify and quantify potential impacts of the X-ray machine in the electric power distribution system. Analyzes and discussions are based on actual measurements obtained in an X-ray apparatus terminals. © 2014 IEEE.
Keywords: harmonics; Modelling; Non-linear loads; Power Quality; X-ray